Liver Histopathological Analysis in The Acute Toxicity Test of Shallot (Allium cepa L.) Peel Extract in Rats (Rattus norvegicus) - Aprilya Pratiwi, Nadilla; Dewi, Rosita; Agustina, Dini; Helianti, Dina; Rachmania, Sheilla (Journal of Agromedicine and Medical Sciences, 2025)
Shallot (Allium cepa L.) contains bioactive compounds with antioxidant effects. In addition to the tuber, the shallot’s peel is a rich source of flavonoids with demonstrated capacity to mitigate oxidative stress. Prior studies have evaluated the antioxidant efficacy of shallot peel in ameliorating organ damage and have established its maximum effective dose. The subsequent step required for its potential therapeutic application is toxicity test. This study aimed to analyze the liver histopathological changes in the acute toxicity test of shallot peel extract (SPE) in rats based on OECD TG 420. This research was an experimental with a post-test-only control group design. Five female rats were used as the control group administered dimethyl sulfoxide (DMSO), while 5 female rats were used in the treatment group administered SPE at 5,000 mg/kg body weight (BW) (one of them had been used for a preliminary test with the same dosage). On day 15, a necropsy was conducted, followed by histopathological observation of the hematoxylin-eosin (HE)-stained liver histopathological slide. The damage to hepatocytes was evaluated using Manja Roenigk criteria. The average histopathological score per liver cell of the control group was 1.226 ± 0.0065 and the treatment group was 1.235±0.0079. The Mann-Whitney test showed that the liver histopathological score of the treatment group was not different from that of the control group (p>0.05). It can be concluded that SPE 5,000 mg/kg does not show acute toxic effects in rats, with LD₅₀ estimated at >5,000 mg/kg according to OECD standards.